Preparation method of novel flaky hollow porous chitin carrier and application of novel flaky hollow porous chitin carrier in immobilized enzyme
The chitin carrier MC-OA with regular shape and hollow porous structure was prepared by repeated freeze-thawing and depolymerization and dispersion methods, which solved the problem of low immobilization efficiency and stability caused by the compact structure of the existing chitin carrier, and achieved the preparation of carriers with high porosity and large pore size, which improved the immobilization efficiency and stability of the enzyme.
Patent Information
- Application Number
- CN202411809320.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing chitin carriers are compact in the drying process, resulting in limited surface area, low porosity and small pore size, which reduces the immobilization efficiency and stability of the enzyme.
The chitin carrier with regular shape and hollow porous structure was prepared by repeated freeze-thawing and depolymerization and dispersion. A mixture of choline chloride and oxalic acid was used as an acidic natural eutectic solvent (NADES), and the mixture of NaOH/urea solution and chitin and freeze-thaw cycle were treated, combined with low-speed stirring of Tween 80-liquid paraffin system, and flake-like hollow porous chitin carrier MC-OA was prepared.
The prepared chitin carrier MC-OA has high porosity, large pore size, and does not require the use of toxic crosslinking agents. It is suitable as an immobilization carrier for enzymes, improving the immobilization efficiency and stability of the enzymes.
Smart Images

Figure CN119613804A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of immobilized enzymes, and relates to a preparation method of a novel sheet-like hollow porous chitosan carrier and application of the carrier in immobilized enzymes. Background Art
[0002] Natural structural carriers are high-quality enzyme immobilization carriers in the field of industrial biocatalysis applications, with characteristics such as higher surface area, easy recycling and reusability. Different nanomaterials, such as metal organic frameworks, carbon nanotubes, silica-based nanoparticles, nanoflowers, nanofiber membranes, graphene oxide and hybrid nanomaterials, are currently widely used carriers for immobilized enzymes. However, with the in-depth study of carrier materials, compared with carriers prepared by nanomaterials, natural polymers have attracted widespread attention due to their low cost and a series of unique properties and advantages. For example, abundant biomass such as chitin has special properties such as non-toxicity, biodegradability and biocompatibility. Chitin is the second most abundant polysaccharide on earth and is mainly found in the shells of crustaceans or the cell walls of some fungi and algae. Chitosan is the second most abundant biomass after cellulose. Although chitosan has excellent biocompatibility, biodegradability and unique biological activity, chitosan extracted from industrial environments has undergone violent reactions with strong acids and alkalis, and its microstructure and internal groups that can bind to proteins have been damaged to a certain extent. Therefore, further modification and processing are needed to prepare chitosan immobilization carrier materials that meet the needs of actual applications.
[0003] Chitosan flake carriers with hollow pores have attracted extensive attention as carriers for enzyme immobilization due to their high surface area-to-mass ratio and excellent mass transfer performance. However, current studies have shown that immobilization techniques that rely on physical adsorption usually have the disadvantages of poor stability of immobilized enzymes and low immobilization efficiency. Therefore, a more attractive immobilization scheme has emerged: the enzyme is covalently bound to a modified chitosan carrier. In practical applications, it is a major challenge to convert chitosan into a flaky, hollow, and porous chitosan carrier while maintaining its inherent properties. During the drying process of chitosan materials, the reduction of capillary forces can cause chitosan aggregation. This causes the chitosan carrier structure to become compact, with the disadvantages of limited surface area, low porosity, and small pore size, thereby reducing the intraparticle diffusion rate of the adsorbate. Therefore, designing a carrier with high porosity and large pore size is the main research direction of chitosan carriers at present. Without using any toxic cross-linking agents, chitosan carriers with regular shapes and hollow porous structures can be prepared through repeated freezing and thawing and depolymerization and dispersion. This carrier material has good biodegradability and is non-toxic, and can be used as a carrier for immobilized enzymes. Summary of the invention
[0004] The first object of the present invention is to provide a method for preparing a sheet-like hollow porous chitosan carrier MC-OA, the steps of which are as follows:
[0005] S1. Choline chloride and oxalic acid were mixed in a molar ratio of 1:3 and stirred continuously at 80°C until the mixture became a stable suspension system to obtain acidic NADES;
[0006] S2. The shrimp shell powder and the acidic NADES prepared in step S1 are mixed in a mass ratio of 1:20, stirred at 80° C. for 2 h, deionized water is added to reduce the viscosity of the system, and then the sample is taken out, the solid component is collected and repeatedly rinsed with deionized water and centrifuged until the pH of the supernatant is neutral, the collected solid component is decolorized with 10% by volume hydrogen peroxide at 80° C., and after the decolorization is completed, it is rinsed with deionized water until the pH of the supernatant is neutral, and the obtained solid is dried at 60° C. to obtain chitosan CCOA;
[0007] S3. Mix natural chitosan CCOA and NaOH / urea solution in a mass ratio of 3:97, freeze into ice at -20°C, then thaw at room temperature, stir vigorously until the chitosan CCOA powder is completely and evenly distributed before the ice layer completely melts, freeze again at -80°C, thaw at room temperature, stir vigorously until the chitosan CCOA powder is completely and evenly distributed before the ice layer completely melts; repeat the freezing, thawing and stirring process until the precipitate is completely dissolved to obtain a chitosan solution;
[0008] S4. The chitosan solution obtained in step S3 was added to the Tween 80-liquid paraffin system at a mass percentage of 30%, and stirred at a low speed for 3 hours. After the stirring, the precipitate was washed with deionized water and anhydrous ethanol, and the precipitate was recovered after the washing;
[0009] S5. Freeze the precipitate recovered in step S4 at -80°C for more than 4 hours, and then freeze-dry it into powder to obtain a sheet-like hollow porous chitosan carrier MC-OA.
[0010] Preferably, the NaOH / urea solution in step S3 is composed of 8 parts by mass of NaOH, 4 parts by mass of urea, and 88 parts by mass of water; and the Tween 80-liquid paraffin system in step S4 is composed of 99 parts by mass of liquid paraffin and 1 part by mass of Tween 80.
[0011] Preferably, the vigorous stirring in step S3 is a stirring speed of 4000 rpm or more; and the low-speed stirring in step S4 is a stirring speed of 2000 rpm or less.
[0012] Preferably, the step S4 of washing the precipitate with deionized water and anhydrous ethanol comprises: first washing with deionized water and centrifuging to remove the liquid paraffin on the surface of the precipitate, then washing with anhydrous ethanol and centrifuging to remove the liquid paraffin and Tween 80 inside the structure, and finally washing with deionized water to remove the liquid paraffin precipitated from the inside of the structure and the anhydrous ethanol remaining on the surface of the precipitate.
[0013] Preferably, the centrifugation is performed at 4000 rpm for 5 min.
[0014] The second object of the present invention is to provide a sheet-like hollow porous chitosan carrier MC-OA prepared by the method.
[0015] The third object of the present invention is to provide a method for preparing immobilized lipase using the sheet-like hollow porous chitin carrier MC-OA, the steps of which are as follows:
[0016] a. Take 0.05g of chitosan carrier MC-OA into a centrifuge tube, add 3mL of pH = 8.0 buffer solution, and use low-power ultrasonic crushing for 10min to make the carrier into microparticle form. After crushing, centrifuge to remove the supernatant and retain the lower layer of the carrier; the low-power ultrasonic crushing conditions are: power 50W, start 1s and stop 2s;
[0017] b. Free lipase, hollow porous chitin carrier MC-OA, and pH = 8.0 buffer solution were mixed in a ratio of 4 mg: 1 g: 10 mL, stirred in an ice bath for 1 h, and placed at 4 ° C for 12 h after stirring;
[0018] c. The precipitate was washed three times by centrifugation with a buffer solution of pH = 8.0 to wash away the residual unimmobilized free lipase, and the precipitate was recovered to obtain the chitin carrier MC-OA immobilized lipase.
[0019] Preferably, the free lipase is porcine pancreatic lipase PPL, Aspergillus niger lipase ANL, Pseudomonas fluorescens lipase PFL, Burkholderia cepacia lipase BCL and Bacillus thermophilus lipase BTL2; the nucleotide sequence of the gene encoding the Bacillus thermophilus lipase BTL2 is shown in SEQ ID NO.1.
[0020] Preferably, the buffer solution is Tris-HCl buffer solution or PBS buffer solution; the stirring for 1 hour under ice bath conditions in step b is stirring for 1 hour under ice bath conditions at 90-100 rpm / min; the centrifugation in steps a and c is centrifugation at 4000 rpm for 5 minutes.
[0021] The fourth object of the present invention is to provide immobilized lipase prepared by the method.
[0022] Beneficial effects of the present invention:
[0023] The present invention mixes a specific chitosan (CCOA) with a NaOH / urea / water solution, dissolves it by a cyclic freeze-thaw method, and then prepares a fibrous porous carrier by a sol-gel method. The fibrous porous carrier has the advantages of a multi-level pore structure, a high specific surface area, and good biocompatibility, and can be used as a carrier material source for protein loading, adsorbents, and drug delivery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 are SEM images of different types of chitin carriers; among them, (a)-(f) are SEM images of MC, MC-LA, MC-CA, MC-MA, MC-TA, and MC-OA, respectively.
[0025] Figure 2 are TEM images of different types of chitin carriers; among them, (a)-(f) are TEM images of MC, MC-LA, MC-CA, MC-MA, MC-TA, and MC-OA, respectively.
[0026] Figure 3 These are the chemical structure results of different types of chitin and chitin carriers prepared therefrom; (a) is the FT-IR result diagram, and (b) is the XRD result diagram.
[0027] Figure 4 The figures are the performance of BTL2 immobilized on different types of chitin carriers; wherein, (a) is the loading content of BTL2 on different types of chitin carriers, and (b) is the enzyme activity after BTL2 is loaded on different types of chitin carriers.
[0028] Figure 5 This is the SEM analysis of BTL2 immobilized on different types of chitin carriers; among them, (a)-(f) are the SEM images of BTL2 immobilized on MC, MC-LA, MC-CA, MC-MA, MC-TA, and MC-OA, respectively.
[0029] Figure 6 This is the CLSM analysis of BTL2 immobilized on different types of chitin carriers; among them, (a)-(f) are the CLSM images of BTL2 immobilized on MC, MC-LA, MC-CA, MC-MA, MC-TA, and MC-OA, respectively.
[0030] Figure 7 It is a universal result of lipase immobilized on MC and MC-OA carriers; (a) is the immobilization efficiency of different types of lipase immobilized on MC and MC-OA carriers, and (b) is the comparison of the enzyme activity of different types of lipase immobilized on MC and MC-OA carriers with the enzyme activity of free enzyme.
[0031] Figure 8This is a graph showing the enzyme activity results of BTL2 immobilized on MC and MC-OA carriers multiple times. DETAILED DESCRIPTION
[0032] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0033] Example 1: Screening of preparation conditions of fibrous porous chitin carrier
[0034] The chitosan used in this embodiment is commercial chitosan (Aladdin Biochemical Technology Co., Ltd.; C104157-100g).
[0035] (1) Screening of the ratio of chitosan to NaOH / urea solution
[0036] A solution with a mass ratio of NaOH:urea:H2O=8:4:88 (hereinafter referred to as NaOH / urea solution) was prepared. 1g, 2g, 3g, 4g, 5g and 6g of chitosan powder were added to 99g, 98g, 97g, 96g, 95g and 94g of NaOH / urea solution according to a solid-liquid mass ratio of 1%, 2%, 3%, 4%, 5% and 6%, respectively. The mixture was frozen into ice at -20°C and thawed at room temperature. Before the ice layer was completely melted, the mixture was stirred vigorously (above 4000rpm) until the chitosan powder was evenly distributed. The mixture was then frozen again at -80°C, and the freezing and thawing (-20°C and -80°C were used alternately) stirring process was repeated until the precipitate was completely dissolved to obtain a chitosan solution of a certain proportion. The number of repeated freezing and thawing depended on whether the chitosan powder was completely dissolved.
[0037] 1g of Tween 80 was added to every 99g of liquid paraffin to prepare a Tween 80-paraffin system. The chitosan solution was slowly poured into the Tween 80-paraffin system at a mass ratio of 30% under ice bath conditions and stirred at a low speed (below 2000rpm) for 3h. After stirring, the precipitate was taken out, first washed with deionized water, centrifuged at 4000rpm for 5min to remove the liquid paraffin on the surface of the precipitate, then washed with anhydrous ethanol, centrifuged at 4000rpm for 5min to remove the liquid paraffin and Tween 80 inside the structure, and finally washed with deionized water to remove the liquid paraffin precipitated from the inside of the structure and the anhydrous ethanol remaining on the surface of the precipitate. The obtained carrier sample was placed at -80℃ for at least 4h and then freeze-dried into powder (i.e., a chitosan carrier was obtained) for immobilizing BTL2 lipase.
[0038] Method for immobilizing BTL2 lipase: 0.05g of chitin carrier prepared under the above different conditions is put into a 10mL centrifuge tube, 3mL of Tris-HCl buffer solution (pH=8.0) is added, and low-power ultrasonic crushing (power 50W, time 10min, start 1s and stop 2s) is used to make the carrier into a microparticle form. After crushing, the supernatant is removed by centrifugation, and the lower layer carrier is retained. According to the ratio of free lipase: carrier: Tris-HCl buffer solution (pH=8.0) = 4mg: 1g: 10mL, stir for 1h under ice bath conditions (stirring speed is 90-100rpm / min), and place at 4℃ for 12h after stirring to immobilize the free BTL2 lipase. After the immobilization process is completed, the precipitate is washed three times with Tris-HCl buffer solution (pH=8.0) at 4000rpm for 5min to wash away the residual unfixed free BTL2 lipase.
[0039] Table 1 Effect of different chitosan contents in chitosan solution on the performance of immobilized enzymes on the carrier
[0040] Chitosan content (%) Enzyme loading (mg / g) Enzyme activity (U / mg) 1% 3.51 164.77±2.92 2% 3.46 159.29±2.07 3% 4.51 242.43±2.33 4% 3.36 15.06±2.94 5% 4 75.92±2.84 6% 3.56 37.51±3.06
[0041] The results in Table 1 show that when the mass ratio of chitosan to NaOH / urea solution is 3:97, the enzyme immobilization performance is the best, the loading amount is 4.51 g / mg, and the enzyme activity is 242.43 U / mg.
[0042] (2) Screening of Chitin Freezing Temperature
[0043] Chitosan was mixed with NaOH / urea solution in a mass ratio of 3:97, and frozen into ice at -20°C, -60°C, -70°C and -80°C, respectively. Before the ice layer completely melted, it was vigorously stirred (above 4000 rpm) until the chitosan powder was evenly distributed, and then frozen again at -20°C, -60°C, -70°C and -80°C, respectively. The freeze-thaw stirring process was repeated until the precipitate was completely dissolved to obtain a chitosan solution of a certain proportion.
[0044] In an ice bath, chitosan solution was slowly poured into the Tween 80-paraffin system at a mass ratio of 30% and stirred at a low speed (below 2000 rpm) for 3 hours. After stirring, the precipitate was taken out, washed with deionized water, centrifuged at 4000 rpm for 5 minutes to remove the liquid paraffin on the surface of the precipitate, then washed with anhydrous ethanol, centrifuged at 4000 rpm for 5 minutes to remove the liquid paraffin and Tween 80 inside the structure, and finally washed with deionized water to remove the liquid paraffin precipitated from the inside of the structure and the anhydrous ethanol remaining on the surface of the precipitate. The obtained carrier sample was frozen at -80°C for at least 4 hours, and then freeze-dried into powder for immobilizing BTL2 lipase (the method refers to the method for immobilizing BTL2 lipase in Example 1 (1)).
[0045] Table 2 Effect of different chitin freezing temperatures on the performance of immobilized enzymes on the carrier
[0046] Dissolving temperature(℃) Enzyme loading (mg / g) Enzyme activity (U / mg) -20 3.45 215.65±1.6 -60 1.22 56.39±0.81 -70 1.51 105.41±1.27 -80 1.18 53.45±0.56
[0047] The results in Table 2 show that when the chitin dissolution temperature is -20°C, the enzyme immobilization performance is the best, the loading amount is 3.45 mg / g, and the enzyme activity is 215.65 U / mg.
[0048] (3) Screening of chitosan solution content in the preparation of immobilized carriers
[0049] Chitosan and NaOH / urea solution were mixed in a mass ratio of 3:97, frozen into ice at -20°C, stirred vigorously (above 4000 rpm) until the chitosan powder was evenly distributed before the ice layer completely melted, and then frozen again at -80°C. The freeze-thaw (-20°C and -80°C were used alternately) stirring process was repeated until the precipitate was completely dissolved to obtain a chitosan solution of a certain proportion.
[0050] In an ice bath, chitosan solution was slowly poured into the Tween 80-paraffin system at a mass ratio of 10%, 20%, 30%, 40%, 50% and 60% and stirred at a low speed (below 2000 rpm) for 3 hours. After stirring, the precipitate was taken out, washed with deionized water, centrifuged at 4000 rpm for 5 minutes to remove the liquid paraffin on the surface of the precipitate, then washed with anhydrous ethanol, centrifuged at 4000 rpm for 5 minutes to remove the liquid paraffin and Tween 80 inside the structure, and finally washed with deionized water to remove the liquid paraffin precipitated from the inside of the structure and the anhydrous ethanol remaining on the surface of the precipitate. The obtained carrier sample was frozen at -80°C for at least 4 hours, and then lyophilized into powder for immobilizing BTL2 lipase (the method refers to the method for immobilizing BTL2 lipase in Example 1 (1)).
[0051] Table 3 Effect of different chitin solution contents on the immobilized enzyme performance of the carrier
[0052] Mass ratio (%) Enzyme loading (mg / g) Enzyme activity (U / mg) 10 4 164.51±1.09 20 4 169.79±1.41 30 3.45 242.71±1.6 40 4 232.98±1.77 50 3.31 109.79±1.41 60 3.26 101.74±1.71
[0053] The results in Table 3 show that when the chitosan solution content is 30%, the enzyme immobilization performance is the best, the loading amount is 3.45 mg / g, and the enzyme activity is 242.71 U / mg.
[0054] (4) Screening of stirring time in the preparation of immobilized carriers
[0055] Chitosan and NaOH / urea solution were mixed in a mass ratio of 3:97, frozen into ice at -20°C, stirred vigorously (above 4000 rpm) until the chitosan powder was evenly distributed before the ice layer completely melted, and then frozen again at -80°C. The freeze-thaw (-20°C and -80°C were used alternately) stirring process was repeated until the precipitate was completely dissolved to obtain a chitosan solution of a certain proportion.
[0056] In an ice bath, chitosan solution was slowly poured into the Tween 80-paraffin system at a mass ratio of 30% and stirred at a low speed (below 2000 rpm) for 1, 2, 3, 4, 5 and 6 hours respectively. After stirring, the precipitate was taken out, washed with deionized water, centrifuged at 4000 rpm for 5 minutes to remove the liquid paraffin on the surface of the precipitate, then washed with anhydrous ethanol, centrifuged at 4000 rpm for 5 minutes to remove the liquid paraffin and Tween 80 inside the structure, and finally washed with deionized water to remove the liquid paraffin precipitated from the inside of the structure and the anhydrous ethanol remaining on the surface of the precipitate. The obtained carrier sample was frozen at -80°C for at least 4 hours, and then freeze-dried into powder for immobilizing BTL2 lipase (the method refers to the method for immobilizing BTL2 lipase in Example 1 (1)).
[0057] Table 4 Effect of different stirring times on the performance of immobilized enzymes on the carrier
[0058] Stirring time (h) Enzyme loading (mg / g) Enzyme activity (U / mg) 1 4 160.98±2.42 2 4 165.88±2.07 3 3.36 242.71±2.33 4 4 236.42±2.64 5 3.48 165.50±2.84 6 3.56 245.22.±2.06
[0059] The results in Table 4 show that when the stirring time is 3h, the enzyme loading is 3.36mg / g and the enzyme activity is 242.71U / mg; when the stirring time is 6h, the enzyme loading is 3.56mg / g and the enzyme activity is 245.22U / mg. Both stirring for 3h and stirring for 6h can obtain immobilized enzymes with good performance, and the difference is not large, so choosing 3h sample preparation can save time cost.
[0060] By dissolving different amounts of commercial chitin and preparing chitin carriers, the immobilized enzyme was optimized and the optimal solution for preparing the chitin carrier was determined as follows: the solid-liquid mass ratio of chitosan to NaOH / urea solution (calculated by mass ratio, NaOH:urea:H2O=8:4:88) was 3:97 (i.e., the chitosan content was 3%), frozen into ice at -20°C, and stirred vigorously (above 4000 rpm) until the chitosan powder was evenly distributed before the ice layer completely melted, and then frozen again at -20°C, and the freeze-thaw (-20°C and -80°C were used alternately) stirring process was repeated until the precipitate was completely dissolved to obtain a chitosan solution. Slowly pour 30g chitosan solution under ice bath conditions and stir at low speed (below 2000rpm) for 3h. After stirring, take out the precipitate and wash it with deionized water, centrifuge it at 4000rpm for 5min to remove the liquid paraffin on the surface of the precipitate, then wash it with anhydrous ethanol, centrifuge it at 4000rpm for 5min to remove the liquid paraffin and Tween 80 inside the structure, finally wash it with deionized water to remove the liquid paraffin precipitated from the inside of the structure and the anhydrous ethanol remaining on the surface of the precipitate, freeze the obtained precipitate at -80℃ for more than 4h, and then freeze it into powder to obtain the chitosan carrier. The immobilization performance analysis shows that the maximum protein loading is 4.51mg / g and the maximum enzyme activity is 242.71±2.33U / mg.
[0061] Example 2: Preparation of shrimp shell-derived carrier
[0062] Choline chloride-lactic acid (CCLA, molar ratio of 1:1), choline chloride-malic acid (CCMA, molar ratio of 1:3), choline chloride-citric acid (CCCA, molar ratio of 1:3), choline chloride-tartaric acid (CCTA, molar ratio of 1:3) and choline chloride-oxalic acid (CCOA, molar ratio of 1:3) were continuously stirred at 80°C until the mixture became a stable suspension system, and an acidic natural deep eutectic solvent (NADES) was prepared. The prepared acidic NADES was used to pretreat shrimp shell powder to extract chitosan. The steps of extracting chitosan are as follows: shrimp shell powder and acidic NADES are mixed in a mass ratio of 1:20, stirred at 80°C for 2h, deionized water is added to reduce the viscosity of the system and then the sample is taken out, the solid components are collected and repeatedly rinsed with deionized water and centrifuged until the pH of the supernatant is neutral, the collected solid components are decolorized with 10% hydrogen peroxide at 80°C, and after decolorization, they are rinsed with deionized water until the pH of the supernatant is neutral, and the obtained solid is dried at 60°C to obtain chitosan.
[0063] Chitosan solutions were prepared using the different types of chitosan and commercial chitosan according to the optimal solution screened in Example 1, and the optimal carrier preparation method was repeated to prepare chitosan carriers. The carriers prepared from different types of chitosan were named MC-LA, MC-MA, MC-CA, MC-TA, and MC-OA, respectively, and the carrier prepared from commercial chitosan was named MC.
[0064] SEM results of different types of chitin carriers are shown in Figure 2. Figure 1 As shown in the figure, all six carriers show a microscopic state in which nanoparticles are condensed or combined into fibers that are entangled with each other. Figure 1 As shown in (a), due to the high purity of commercial chitin, impurities have less interference with the carrier (MC) formation process, so the particles are evenly distributed and the carrier is formed by the aggregation of nanoparticles. Figure 1 The carriers of (b)-(e) are MC-LA, MC-CA, MC-MA, and MC-TA, respectively, which are in the form of entangled fibers. This may be because the chitosan used is extracted using an acidic natural deep eutectic solvent (NADES), and its purity is lower than that of commercial chitosan. The chitosan nanoparticles are disturbed by impurities and first form chitosan fibers, which are then entangled into the form of carrier particles through intermolecular forces such as electrostatic adsorption. Figure 1 The carrier of (f) is MC-OA, which is an irregular polyhedron. The reason for its formation may be the presence of calcium oxalate crystals in chitin. The chitin nanoparticles condense around the calcium oxalate crystals to form an irregular polyhedron that aggregates along the edges of the calcium oxalate crystals. It is worth noting that CCOA chitin containing calcium oxalate impurities produces carriers with smaller particle sizes. The reason for this phenomenon is speculated to be that the presence of calcium oxalate crystals controls the direction of carrier formation to a certain extent. Calcium oxalate, as the core of the carrier, has the ability to guide the carrier preparation reaction to generate carriers with smaller particle sizes.
[0065] The results of TEM are as follows Figure 2 , it can be observed that there is a lot of space in the inner structure of the six carriers. Figure 2 The result (a) in the figure shows that there are a large number of holes in the internal space of the carrier MC that run through the entire carrier. The formation of the internal space may be that after the higher purity chitosan is dissolved, the dispersion is more uniform during the preparation of the carrier. When the reaction system begins to condense to form the carrier, the nanoparticles aggregate according to the direction of the chitosan molecule crystallization. The α-chitosan molecules in nature tend to form strip-shaped or rod-shaped crystals when they crystallize. Therefore, the carrier MC may be composed of multiple α-chitosan crystals connected to form a structure with a large number of holes inside. Figure 2From (b)-(e) in the figure, we can see that these four carriers (MC-LA, MC-CA, MC-MA, and MC-TA) also have pores running through them, but the number of pores is relatively small. The reason is that the presence of impurities affects the aggregation of nanoparticles. During the carrier formation stage, the chitosan nanoparticles agglomerate prematurely to generate carriers with larger particle sizes, which limits the formation of internal pores. Figure 2 In (f), we can also observe that there are a lot of pores inside the carrier MC-OA. Combined with the results of SEM, we can see that calcium oxalate crystals, as the core of the carrier, trigger the aggregation of nanoparticles. At the same time, the calcium oxalate crystal particles as the core are small and not enough to support chitin to condense into a larger carrier, so a lot of pores are retained in the internal space.
[0066] The FT-IR results of the carrier are as follows Figure 3 As shown in (a) in the experiment, the difference between the selected chitosan raw materials and the prepared carrier functional groups was investigated. The results showed that the optimal preparation method of the carrier in Example 1 would not affect the properties of chitosan, and the carrier retained the stable physical and chemical properties of chitosan. In addition, the crystal structure information of 5 chitosan samples (CCLA, CCMA, CCCA, CCTA, CCOA) and the carrier (MC-LA, MC-MA, MC-CA, MC-TA, MC-OA) was compared by XRD, and the crystal form changes of chitosan during the preparation of the carrier were compared. The results are shown in FIG. Figure 3 As shown in (b) in the figure. The carrier prepared from the corresponding chitin sample does not affect the crystal form of chitin, and the XRD spectra of all carriers show the characteristic peaks of α-chitin. It is worth noting that the results of the carrier MC-OA are consistent with those of the raw material CCOA, and the characteristic peaks of calcium oxalate crystals also appear. Therefore, the carrier sample retains the unique synergistic effect of CCOA in immobilizing enzymes to a certain extent.
[0067] The results of the Zeta potential and particle size analysis of different types of carrier samples are shown in Table 5. The absolute value of the Zeta potential can be used to determine the dispersion stability of the particles. The absolute values of the Zeta potential of the carriers MC, MC-CA, and MC-TA are around 5, so these three carriers will quickly aggregate or condense in the solution state. The absolute values of the Zeta potential of the other three carriers are greater than ±10, so these three carriers need to stand for a longer time in the solution state before aggregation or condensation occurs. The dispersion stability of the carrier is better than that of MC, MC-CA, and MC-TA. The results of the particle size analysis show that the carrier preparation method used can prepare micron-level carriers. Among them, the particle sizes of MC-TA and MC-OA are smaller because the chitin raw materials CCTA and CCOA used are more broken during the extraction process, and the chitin dissolution reaction is more sufficient. It is easy to disperse and form micron particles with smaller particle sizes during the carrier preparation process. However, due to the relatively low degree of solubility, the other four carrier samples condense in advance during the preparation process, generating particles with larger particle sizes.
[0068] Table 5 Zeta potential and particle size of chitin carrier
[0069] Sample name Zeta potential (mV) Particle size (nm) MC -5.92±1.63 2484.66±366.14 MC-LA 13.56±1.11 4423.00±721.94 MC-CA 6.87±1.03 1360.33±74.77 MC-MA 11.47±3.63 5884.33±1075.40 MC-TA 5.28±2.50 926.70±20.31 MC-OA 16.13±1.18 979.76±47.38
[0070] Example 3: Enzyme immobilized on chitin carrier
[0071] Take 0.05g of different types of chitin carriers and put them into 10mL centrifuge tubes, add 3mL Tris-HCl buffer solution (pH=8.0), and use low-power ultrasonic crushing (power 50W, time 10min, start 1s and stop 2s) to make the carrier into microparticle form. After crushing, centrifuge at 4000rpm for 5min to remove the supernatant and retain the lower carrier. Mix according to the ratio of free lipase: carrier: Tris-HCl buffer solution (pH=8.0) = 4mg: 1g: 10mL, stir for 1h under ice bath conditions (stirring speed is 90-100rpm / min), and place at 4℃ for 12h after stirring to immobilize the free lipase. After the immobilization process is completed, use Tris-HCl buffer solution (pH=8.0) 4000rpm centrifugation for 5min to wash the precipitate three times to wash away the residual unfixed free lipase, collect the washed supernatant for use (determine the unfixed protein content and enzyme activity), and store the carrier-immobilized enzyme at 4℃.
[0072] The free lipases used in the above steps are porcine pancreatic lipase PPL, Aspergillus niger lipase ANL, Candida lipase CAL, Pseudomonas fluorescens lipase PFL, Burkholderia cepacia lipase BCL and Bacillus thermophilus lipase BTL2, and the specific information is shown in Table 6.
[0073] Table 6 Free lipase related information
[0074]
[0075] (1) Effects of different chitin carriers on the loading capacity and enzyme activity of thermophilic Bacillus lipase BTL2
[0076] Carriers prepared from different types of chitin correspond to different immobilized lipase properties.
[0077] like Figure 4 As shown in (a), the carriers MC and MC-OA have excellent immobilization efficiency for BTL2. The immobilization capacity (enzyme protein loading capacity) of these two carriers for BTL2 is 3.37 times (2.80 mg / g) and 3.39 times (2.82 mg / g) of CCOA (0.83 mg / g). In addition, except that the immobilization efficiency of the MC-CA carrier is similar to that of CCOA, the performance of the immobilized enzymes of the carriers MC-LA, MC-MA, and MC-TA has been improved to a certain extent, which are 2.05 mg / g, 2.32 mg / g, and 1.42 mg / g, respectively, with an improvement range of 1.71-2.79 times.
[0078] After immobilizing BTL2 free enzyme on different types of chitin carriers, enzyme activity was tested under the optimal reaction conditions (pH = 8.0, Tris-HCl buffer solution). Figure 4 As shown in (b), the enzymatic activity of BTL2 immobilized on different types of chitin carriers is weaker than that of the free enzyme. The reason is presumably that the lipase is encapsulated in the internal structure of the carrier. During the enzymatic reaction, the reaction substrate cannot fully contact the active site of the enzyme protein, resulting in reduced enzyme activity. The carrier MC-OA has the same defect, but it is worth noting that when the reaction conditions are changed to PBS buffer solution (pH = 8.0), the enzyme activity of MC-OA can be improved. The reason for this phenomenon may be that when the carrier MC-OA immobilizes the enzyme protein, certain functional groups on the structure affect the structure of the enzyme protein, causing the enzyme protein to change its requirements for reaction conditions, so it needs to be in a PBS buffer system to show activity.
[0079] Figure 5 and Figure 6 The immobilization of enzyme protein on chitin carrier was characterized. The results showed that the protein was successfully loaded into the structure of chitin carrier, and a large number of BTL2 protein crystals were attached to the lamellar stacking structure of the carrier. The existence of the lamellar stacking structure greatly improved the immobilization effect of lipase. At the same time, the enzyme protein was loaded into the interior of the carrier, which hindered the contact between the substrate and the active center of the enzyme to a certain extent, resulting in the inhibition of the activity recovery of the immobilized enzyme.
[0080] (2) Effects of optimized chitin carrier on the immobilization performance and enzyme activity of different types of lipase
[0081] The immobilization efficiency of commercial lipase on carrier is as follows Figure 7 As shown in (a), the immobilization efficiency of carrier MC-OA for lipase is better than that of carrier MC. The reason for this phenomenon may be that the particle size of carrier MC-OA is smaller than that of carrier MC, and it has a larger specific surface area, so it can contact with more enzyme proteins and thus load more lipase. Another reason may be the high enzyme protein loading characteristics of chitin CCOA, the raw material for preparing MC-OA. It is worth noting that carrier MC-OA cannot load lipase CAL. This may be because the prepared carrier is not compatible with the molecular size or surface group of the lipase, and covalent cross-linking cannot occur. The reason why carrier MC cannot load lipase PPL, and the reason why carrier MC-OA successfully loads PPL is speculated to be that the calcium oxalate contained in chitin CCOA has a directionally changed morphology, making it able to adapt to lipase PPL. Figure 7 (b) in the figure shows the enzyme activity of the MC and MC-OA carrier-immobilized enzymes under the respective optimal reaction conditions of the commercial lipase. The results show that since the active center of the commercial lipase is masked, it still cannot effectively induce the enzymatic reaction under the optimal reaction conditions. Therefore, the MC-OA carrier has a certain universality for the loading of lipase, but for the enzyme activity of free BTL2 (128.49U / mg) and the enzyme activity of BTL2 immobilized on the MC carrier (216.71±2.47U / mg), the MC-OA carrier effectively improves the enzyme activity of BTL2 when loaded with BTL2, and the enzyme activity is 245.43±2.51U / mg ( Figure 7 (b) in the figure.
[0082] (3) Evaluation of the reusability of enzymes immobilized on chitin carriers after optimization
[0083] Reusability is a key parameter in industrial biocatalysis, which refers to the ability of immobilized enzymes to maintain catalytic activity and structural stability over multiple reaction cycles. This ability can minimize enzyme waste, reduce production costs, and solve the problems of free enzymes such as inactivation and difficulty in recycling. Figure 8The reproducibility of the immobilized enzyme activity was verified to evaluate its potential for recycling. Although the immobilized BTL2 showed good stability during repeated use, its activity gradually decreased over time and with increasing frequency of use. This decline in enzyme activity can be attributed to two main factors: (1) structural changes or denaturation of the enzyme due to repeated use; and (2) shedding or degradation of the immobilization sites, which reduces the number of enzyme molecules with catalytic activity. In the case of immobilized enzymes using MC and MC-OA carriers, the immobilized BTL2 retained more than 50% of its relative activity after reaching the maximum number of cycles of use for the 10th and 12th times, respectively, and the enzyme activity decreased to 121.5 and 125.01 U / mg, respectively, accounting for 56.34% and 51.51% of the initial enzyme activity. After this point, the effect of further restoring the enzyme activity was minimal, indicating that there is a threshold for the reusability of the immobilized enzyme.
[0084] In summary, the loading efficiency of the immobilized lipase on the chitin carrier of the present invention is significantly improved, wherein the carriers MC and MC-OA increase the immobilization efficiency of the enzyme to 3.37 times and 3.39 times, respectively. The enzyme activity of BTL2 after MC-OA immobilization can reach up to 1.91 times the enzyme activity of free BTL2 under the optimal reaction conditions, proving that the carrier is a good immobilized lipase carrier. The carrier MC-OA prepared using chitin CCOA is superior to the carrier MC in the determination of various performance indicators, proving that the carrier MC-OA retains the activation effect of natural chitin on lipase, and has great development potential as an immobilized lipase carrier. The results of the immobilization of commercial lipases show that the MC-OA carrier has universal applicability to the loading of various lipase proteins, but exhibits excellent performance in improving enzyme activity for BTL2.
Claims
1. A method for preparing a sheet-like hollow porous chitosan carrier MC-OA, characterized in that: Here are the steps: S1. Choline chloride and oxalic acid were mixed in a molar ratio of 1:3 and stirred continuously at 80°C until the mixture became a stable suspension system to obtain acidic NADES; S2. The shrimp shell powder and the acidic NADES prepared in step S1 are mixed in a mass ratio of 1:20, stirred at 80° C. for 2 h, deionized water is added to reduce the viscosity of the system, and then the sample is taken out, the solid component is collected and repeatedly rinsed with deionized water and centrifuged until the pH of the supernatant is neutral, the collected solid component is decolorized with 10% by volume hydrogen peroxide at 80° C., and after the decolorization is completed, it is rinsed with deionized water until the pH of the supernatant is neutral, and the obtained solid is dried at 60° C. to obtain chitosan CCOA; S3. Mix natural chitosan CCOA and NaOH / urea solution in a mass ratio of 3:97, freeze into ice at -20°C, then thaw at room temperature, stir vigorously until the chitosan CCOA powder is completely and evenly distributed before the ice layer completely melts, freeze again at -80°C, thaw at room temperature, stir vigorously until the chitosan CCOA powder is completely and evenly distributed before the ice layer completely melts; repeat the freezing, thawing and stirring process until the precipitate is completely dissolved to obtain a chitosan solution; S4. The chitosan solution obtained in step S3 was added to the Tween 80-liquid paraffin system at a mass percentage of 30%, and stirred at a low speed for 3 hours. After the stirring, the precipitate was washed with deionized water and anhydrous ethanol, and the precipitate was recovered after the washing; S5. Freeze the precipitate recovered in step S4 at -80°C for more than 4 hours, and then freeze-dry it into powder to obtain a sheet-like hollow porous chitosan carrier MC-OA.
2. The method according to claim 1, characterized in that The NaOH / urea solution in step S3 is composed of 8 parts by mass of NaOH, 4 parts by mass of urea, and 88 parts by mass of water; the Tween 80-liquid paraffin system in step S4 is composed of 99 parts by mass of liquid paraffin and 1 part by mass of Tween 80.
3. The method according to claim 1, characterized in that The vigorous stirring in step S3 is a stirring speed of more than 4000 rpm; the low-speed stirring in step S4 is a stirring speed of less than 2000 rpm.
4. The method according to claim 1, characterized in that: The step S4 of washing the precipitate with deionized water and anhydrous ethanol comprises: first washing with deionized water and centrifuging to remove the liquid paraffin on the surface of the precipitate, then washing with anhydrous ethanol and centrifuging to remove the liquid paraffin and Tween 80 inside the structure, and finally washing with deionized water to remove the liquid paraffin precipitated from the inside of the structure and the anhydrous ethanol remaining on the surface of the precipitate.
5. The method according to claim 4, characterized in that The centrifugation is performed at 4000 rpm for 5 minutes.
6. A sheet-like hollow porous chitosan carrier MC-OA prepared by the method according to any one of claims 1 to 5.
7. A method for preparing immobilized lipase using the sheet-like hollow porous chitosan carrier MC-OA according to claim 6, characterized in that: Here are the steps: a. Take 0.05g of the hollow porous chitin carrier MC-OA into a centrifuge tube, add 3mL of pH = 8.0 buffer solution, and use low-power ultrasonic crushing for 10min to make the carrier into microparticle form. After crushing, centrifuge to remove the supernatant and retain the lower carrier; the low-power ultrasonic crushing conditions are: power 50W, start 1s and stop 2s; b. Free lipase, hollow porous chitin carrier MC-OA, and pH = 8.0 buffer solution were mixed in a ratio of 4 mg: 1 g: 10 mL, stirred in an ice bath for 1 h, and placed at 4 ° C for 12 h after stirring; c. The precipitate was washed three times by centrifugation with a buffer solution of pH = 8.0 to wash away the residual unimmobilized free lipase, and the precipitate was recovered to obtain the chitin carrier MC-OA immobilized lipase.
8. The method according to claim 7, characterized in that The free lipases are porcine pancreatic lipase PPL, Aspergillus niger lipase ANL, Pseudomonas fluorescens lipase PFL, Burkholderia cepacia lipase BCL and Bacillus thermophilus lipase BTL2; the nucleotide sequence of the coding gene of the Bacillus thermophilus lipase BTL2 is shown in SEQ ID NO.
1.
9. The method according to claim 7, characterized in that: The buffer solution is a Tris-HCl buffer solution or a PBS buffer solution; the stirring for 1 hour under ice bath conditions in step b is stirring for 1 hour under ice bath conditions at 90-100 rpm / min; the centrifugation in steps a and c is centrifugation at 4000 rpm for 5 minutes.
10. Immobilized lipase prepared by the method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Method for preparing regenerated chitin microspheres
CN104624130A
Method for separating insect proteins, oil and chitin in one step by natural deep-eutectic solvents, and application thereof
CN110183510A
Chitin microsphere loaded nano zero-valent iron material as well as preparation method and application thereof
CN115739034A
Method for homogeneously preparing hydroxypropyl modified chitin with low degree of deacetylation
WO2015161814A1